2013
DOI: 10.1016/j.tube.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

pncA gene expression and prediction factors on pyrazinamide resistance in Mycobacterium tuberculosis

Abstract: Summary Background Mutations in the pyrazinamidase (PZAse) coding gene, pncA, have been considered as the main cause of pyrazinamide (PZA) resistance in Mycobacterium tuberculosis. However, recent studies suggest there is no single mechanism of resistance to PZA. The pyrazinoic acid (POA) efflux rate is the basis of the PZA susceptibility Wayne test, and its quantitative measurement has been found to be a highly sensitive and specific predictor of PZA resistance. Based on biological considerations, the POA ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…Most interestingly, the majority of those cases were associated with mutations in three specific regions of the pncA gene (codon 51 to 76, codon 130 to 142, and codon 163 to 180). As previously reported (25), these three pncA regions related to high-level PZA resistance might be associated with the activity of PZase. As structural models of the PZase have revealed, these three specific regions are located in loop 4, loop 7, and loop 10, which have been proven to be the part of PZase active-site region (loop 7) and the metal coordination site (loop 4) (26).…”
Section: Discussionsupporting
confidence: 74%
“…Most interestingly, the majority of those cases were associated with mutations in three specific regions of the pncA gene (codon 51 to 76, codon 130 to 142, and codon 163 to 180). As previously reported (25), these three pncA regions related to high-level PZA resistance might be associated with the activity of PZase. As structural models of the PZase have revealed, these three specific regions are located in loop 4, loop 7, and loop 10, which have been proven to be the part of PZase active-site region (loop 7) and the metal coordination site (loop 4) (26).…”
Section: Discussionsupporting
confidence: 74%
“…In a recent study, the prevalence of PZA resistance was 0%–9% in cases of drug-sensitive TB, and 31%–89% among MDR-TB isolates. The study found a significant increase in the prevalence of PZA-resistant TB with increased resistance to other drugs (3031). Further studies studying the prevalence, cause, and relation between MDR-TB and PZA-resistant TB are warranted.…”
Section: Discussionmentioning
confidence: 97%
“…tuberculosis drug-resistant strains have been described to increase the expression of efflux pumps to enable their survival and persistence in the presence of antibiotics (41)(42)(43)(44). Although we did not explore drug-resistant strains in this study, additional research to try and reverse drug resistance using TIM and clinical isolates of M. tuberculosis and evaluation of these in broth and infected macrophage cultures, as well as in vivo studies, are warranted.…”
Section: Discussionmentioning
confidence: 98%